Maternal nutrient metabolism in the liver during pregnancy - Fang, Hongxu; Li, Qingyang; Wang, Haichao; Ren, Ying; Zhang, Leying; Yang, Ling (Frontiers in Endocrinology, 2024)
The liver plays pivotal roles in nutrient metabolism, and correct hepatic adaptations are required in maternal nutrient metabolism during pregnancy. In this review, hepatic nutrient metabolism, including glucose metabolism, lipid and cholesterol metabolism, and protein and amino acid metabolism, is first addressed. In addition, recent progress on maternal hepatic adaptations in nutrient metabolism during pregnancy is discussed. Finally, the factors that regulate hepatic nutrient metabolism during pregnancy are highlighted, and the factors include follicle-stimulating hormone, estrogen, progesterone, insulin-like growth factor 1, prostaglandins fibroblast growth factor 21, serotonin, growth hormone, adrenocorticotropic hormone, prolactin, thyroid stimulating hormone, melatonin, adrenal hormone, leptin, glucagon-like peptide-1, insulin glucagon and thyroid hormone. Our vision is that more attention should be paid to liver nutrient metabolism during pregnancy, which will be helpful for utilizing nutrient appropriately and efficiently, and avoiding liver diseases during pregnancy.